The Influence of Leadership on Work Motivation and Its Effect on Nurses’ Performance in Ward Unit of Morotai Island District Hospital - Idi, Sunardi; Hidayah, Nur (RA Journal of Applied Research, 2020)
Background: Performance of nurses in hospitals is very important because it affects the quality of patient services and overall hospital performance. The purpose of this study was to determine the effect of the leadership of nurses on nurses' work motivation and their impact on nurse performance. Subjects and Method: This study uses a quantitative approach. Samples were 100 nurses in the inpatient room of RSUD Kabupaten Pulau Morotai. The sampling technique is simple random sampling. Data collection techniques using a questionnaire. Data analysis techniques using path analysis. Result: The results of the path analysis show that there is a positive influence on the leadership of nurses on nurse work motivation, there is no influence on the leadership of nurses on the performance of nurses and there is a positive influence on work motivation on the performance of nurses inpatients at the RSUD Kabupaten Pulau Morotai. Conclusion: Nurse performance can be improved through a good leadership role that is able to motivate nurses to work optimally.